2014
DOI: 10.1155/2014/769708
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Surface Active Agents in the Environment

Abstract: Due to the specific structure of surfactants molecules they are applied in different areas of human activity (industry, household). After using and discharging from wastewater treatment plants as effluent stream, surface active agents (SAAs) are emitted to various elements of the environment (atmosphere, waters, and solid phases), where they can undergo numerous physic-chemical processes (e.g., sorption, degradation) and freely migrate. Additionally, SAAs present in the environment can be accumulated in living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 105 publications
2
78
0
3
Order By: Relevance
“…Moreover, the trend that a higher concentration was determined for compounds with longer alkyl chains can clearly be observed. Research result confirm that LAS C 12 and LAS C 13 (more hydrophobic compounds than LAS C 10 and LAS C 11 ) have greater sorption ability on the solid phase (sediment) in aquatic ecosystems (Ying 2006;Sablayrolles et al 2009;Olkowska et al 2014). At sampling points O-1, O-6 and O-8 levels of determined anionic surfactants were highest.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…Moreover, the trend that a higher concentration was determined for compounds with longer alkyl chains can clearly be observed. Research result confirm that LAS C 12 and LAS C 13 (more hydrophobic compounds than LAS C 10 and LAS C 11 ) have greater sorption ability on the solid phase (sediment) in aquatic ecosystems (Ying 2006;Sablayrolles et al 2009;Olkowska et al 2014). At sampling points O-1, O-6 and O-8 levels of determined anionic surfactants were highest.…”
Section: Resultssupporting
confidence: 53%
“…It should be mentioned that in the case of liquidated mines in area of the Bytomka catchment dewatering is also applied so as to ensure the safety of active mines (Lach et al 2004). The impact of pollution from industrial and municipal areas on this ecosystem is observed as changes in the hydrographic network of rivers and the quality of its waters (Trochim 2006;Ruman et al 2014). As a consequence of the previously mentioned aspects the River Kłodnica was selected as a research area.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations